INTELLEKTUAL MULK HUQUQINI HIMOYA QILISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rapid introduction of modern information and innovative technologies to economic sectors, social and other fields by applying the results of intellectual activity is considered one of the important conditions for the rapid development of the Republic of Uzbekistan... The rapid introduction of modern information and innovative technologies to economic sectors, social and other fields by applying the results of intellectual activity is considered one of the important conditions for the rapid development of the Republic of Uzbekistan.